Linking Globalization and the Culture of Violence in Africa: Implications for Security in Nigeria - Musa, Auwalu; Boya, Iya Wakili; Jibrilla, Aisha Babangida; Ibrahim, Hajara Mohammed; Isa, Hajara Abubakar; Abdulhamid, Hassan; David, Philomena Zichat (Kashere Journal of Politics and International Relations, 2024)
The intersection of globalization and the culture of violence in Africa, with particular reference to Nigeria, pose a multifaceted challenge impacting various security dimensions. The infiltration of violent extremism, insurgency, and related phenomena have shaped a complex security landscape, affecting military readiness, political stability, economic development, environmental sustainability, psychological well-being, societal cohesion, territorial integrity, and technological resilience. This paper explores the linkage between globalization and the culture of violence in Africa, emphasizing security implications. Qualitative methods, including the analysis of books, journal articles, internet sources, etc., were employed for data collection, with content analysis as the chosen analytical method. The findings reveal that globalization, through its economic, cultural, and technological dimensions, have transformed and intensified violence within Nigerian communities. The paper underscores how global interconnectedness has facilitated the dissemination of extremist ideologies, heightened ethnic tensions, and worsened existing conflicts, fostering a conducive environment for violence. Furthermore, the paper delineates the nuanced implications of this phenomenon on Nigerian security, highlighting the significant challenges posed by the emergence of insurgent groups like Boko Haram and other internal strife to the country's stability and governance structures. The paper recommends comprehensive strategies beyond conventional security measures to address the impacts of globalization-induced violence in Nigeria. It advocates for multifaceted approaches encompassing social, economic, and political dimensions to effectively tackle the intricate security threats stemming from the culture of violence induced by globalization.